2015
DOI: 10.1108/bepam-10-2013-0045
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of construction organisations’ competitive strategies and performance

Abstract: Purpose – The essence of strategy formulation is to assist an organisation obtain a strategic fit with its environment and help enhance organisational continuous improvement in achieving performance excellence. The purpose of this paper is to investigate the type of competitive strategies used by construction organisations in attaining their strategic goals in South Africa. Design/methodology/approach – The study employs an inductive res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
6
25
0
Order By: Relevance
“…There is a debate between the two schools of thoughts: one gives value to pursuing DS while the other favors CLS. For example, some studies argue that only DS improves firms' performance directly (Teti et al, 2014; Yuliansyah et al, 2016) while other studies suggest the importance for CLS (Oyewobi, Windapo, & James, 2015; Allen & Helms, 2006). In fact, both CLS and DS improve SME's performance.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a debate between the two schools of thoughts: one gives value to pursuing DS while the other favors CLS. For example, some studies argue that only DS improves firms' performance directly (Teti et al, 2014; Yuliansyah et al, 2016) while other studies suggest the importance for CLS (Oyewobi, Windapo, & James, 2015; Allen & Helms, 2006). In fact, both CLS and DS improve SME's performance.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Moreover, Hitt, Carnes, and Xu (2016) describe that differential strategy of business firms enable them to sort a maintainable competitive position in the turbulent market that is essential for high market performance. SMEs pursuing DS generate higher value over firms pursuing only CLS (Oyewobi et al, 2015; Teti et al, 2014). So we hypothesize:Hypothesis Differentiation strategy is positively related to financial performance of Emerging SMEs . Hypothesis Differentiation strategy is positively related to nonfinancial performance of Emerging SMEs .…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Chinese firms often tend to follow cost-based competitive strategies instead of a differentiating-based strategy which may require high financial capabilities and resources (Parnell et al 2015). Both strategies of Porter-cost leadership and differentiation-based-have a significant influence on the financial and non-financial performance of SMEs (Oyewobi et al 2015). Empirical evidence indicated that competitive strategy has a significant influence on firm performance González-Rodríguez et al 2018;Lechner and Gudmundsson 2014).…”
Section: Competitive Advantage and Sme Performancementioning
confidence: 99%
“…It is clear that each company has its particularities and therefore there would not be two equal strategies since each company has different objectives, available resources, capabilities, different areas and scope (Arli, Rundle-Thiele & Lasmono, 2015;Oyewobi, Windapo & James, 2015). However, the companies that have similar strategies share similar products and have a similar story, but they also compete to develop new resources and capabilities.…”
Section: Successfulness Of Differentiation Strategymentioning
confidence: 99%